Kaili Women in Strengthening The Family Economy - Utama, Roman Rezki; Roslinwati, Roslinwati (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
The role of women in development is very significant from a social, cultural, and economic perspective. The existence of women has an important role in both the family andÂ society. This study aims to analyze the role of women Kaili business actors in the Palu City Forest in providing family economic strengthening from a social and cultural perspective. This study was designed using a quantitative approach. The population of this research is Kaili women who have businesses in the Palu City Forest. The sample of this research is women Kaili business actors in the Palu City Forest, with a total of 183 respondents. Data collection techniques consist of observation, questionnaires, and documentation. Data analysis uses descriptive statistical analysis. The results of the study show that women Kaili business actors in the Palu City Forest play a role in encouraging the strengthening of the family economy. From a social perspective, women Kaili business actors have a high level of social bounding, which is indicated by the kinship of women Kaili with other families that creates empathy and togetherness. This can also encourage the strengthening of the family economy. Meanwhile, from a cultural perspective, the level of inequality among women Kaili business actors in the Palu City Forest is strongly influenced by culture. This inequality means that women Kaili business actors in the Palu City Forest do not feel competitive and different from other business actors, so they feel relaxed in doing business and have an impact on strengthening the family economy.Peran perempuan dalam pembangunan sangat signifikan dilihat dari sudut pandang sosial, budaya, dan ekonomi. Keberadaan perempuan mempunyai peranan penting baik dalam keluarga maupun masyarakat. Penelitian ini bertujuan untuk menganalisis peran perempuan pelaku usaha Kaili di Hutan Kota Palu dalam memberikan penguatan ekonomi keluarga dari segi sosial dan budaya. Penelitian ini dirancang dengan menggunakan pendekatan kuantitatif. Populasi penelitian ini adalah ibu-ibu Kaili yang mempunyai usaha di Hutan Kota Palu. Sampel penelitian ini adalah perempuan pelaku usaha Kaili di Hutan Kota Palu yang berjumlah 183 responden. Teknik pengumpulan data terdiri dari observasi, angket, dan dokumentasi. Analisis data menggunakan analisis statistik deskriptif. Hasil penelitian menunjukkan bahwa perempuan pelaku usaha Kaili di Hutan Kota Palu berperan dalam mendorong penguatan perekonomian keluarga. Dari segi sosial, perempuan pelaku usaha Kaili mempunyai tingkat ikatan sosial yang tinggi, ditandai dengan kekerabatan perempuan Kaili dengan keluarga lain sehingga menimbulkan rasa empati dan kebersamaan. Hal ini juga dapat mendorong penguatan perekonomian keluarga. Sedangkan dari segi budaya, tingkat ketimpangan di kalangan perempuan pelaku usaha Kaili di Hutan Kota Palu sangat dipengaruhi oleh budaya. Ketimpangan tersebut membuat perempuan pelaku usaha Kaili di Hutan Kota Palu tidak merasa kompetitif dan berbeda dengan pelaku usaha lainnya, sehingga merasa santai dalam berusaha dan berdampak pada penguatan perekonomian keluarga.